Distributed solar photovoltaics in China: Policies and economic performance. (August 2015) - Zhao, Xingang; Zeng, Yiping; Zhao, Di
Abstract: The recent rapid development of distributed PV (photovoltaic) industry in China closely ties to the relevant policies support. This paper reviews some main points of relevant policies including financial support, technology innovation and management improvement. Scenario analysis both in residential sectors and industrial and commercial sectors are taken into account. We calculate IRR (internal rate of return) and static payback period of a specific distributed PV system in China's five cities located in different resource areas. In order to provide a realistic reference for investors, the historical data from real projects are used to calculate the generating capacity. The impacts of relevant policy variables such as subsidies, benchmark price, electricity price and tax on economic performance of distributed PV system are discussed. The results show that distributed PV system with high generation efficiency has produced good economic benefit in both two scenarios under China's current policies. The current policy instruments on distributed PV industry are efficient. At the end of the paper, policy recommendations are offered as references for the government. Highlights: Review China's current relevant policies for distributed PV industry. Use historical data from real PV projects to calculate the generating capacity. Calculate the financial variables of China's distributed PV projects. Discuss the impact of each policy variable on economic performance. Discuss the development prospects of distributed PV.